Evaluasi derajat delirium sebagai prediktor mortalitas pasien usia lanjut dengan delirium yang dirawat di RSUP Sanglah, Bali, Indonesia - Dian Pritasari Jeger; Yosef Samon Sugi; I Gusti Putu Suka Aryana; RA Tuty Kuswardhani; I Nyoman Astika; Ida Bagus Putrawan; Ni Ketut Rai Purnami (DiscoverSys Inc., 2020)
Background: Delirium is an acute attention and cognitive disorder that occurs in elderly patients. The disorder is usually very serious, often goes unrecognized, and is usually fatal. Diagnosis requires a complete cognitive assessment and a history of acute symptoms. Despite the management of the cause, patients with delirium do not always recover. The aim of this study was to determine the correlation between the degree of delirium and the incidence of death in geriatric patients who were admitted to Sanglah General Hospital.Methods: A retrospective cohort study was conducted during November 2014-February 2015 of consecutive patients with delirium aged over 60 years. The degree of delirium was measured by the Memorial Delirium Assessment Scale (MDAS) and Charlson's-Age Comorbidity Index (CACI). These patients were followed periodically and then a bad outcome was determined, namely death while being treated. The association between the severity of delirium and clinical outcome was evaluated using the Pearson test. The results are said to be significant if the p value <0.05 on SPSS version 21 for Windows.Results: The prevalence of delirium in Sanglah General Hospital was mild delirium (48.4%), moderate delirium (28.1%), and severe delirium (23.4%). There was a significant difference in the prevalence of the degree of delirium based on age (p <0.05), but not on gender (p = 0.752). There was a significant difference in the incidence of death based on age (p = 0.045) and degree of delirium (p = 0.01). There was a moderate positive correlation between the degree of delirium and the incidence of death (p = 0.02; r = 0.373).Conclusion: There is a significant relationship between the degree of delirium and the incidence of death in geriatric patients hospitalized in Sanglah General Hospital. Latar belakang: Delirium merupakan gangguan perhatian dan kognitif akut yang terjadi pada pasien usia tua. Gangguan tersebut biasanya sangat serius, sering tidak dikenali, dan biasanya sangat fatal. Penegakan diagnosis memerlukan penilaian kognitif yang lengkap dan riwayat adanya gejala yang timbul secara akut. Meskipun diberikan penatalaksanaan terhadap penyebabnya, pasien dengan delirium tidak selalu pulih. Tujuan dari penelitian ini adalah untuk menentukan korelasi antara derajat delirium dengan insiden kematian pada pasien geriatri yang dirawat di RSUP Sanglah.Metode: Penelitian kohort retrospektif dilakukan selama bulan November 2014-Februari 2015 terhadap pasien dengan delirium yang berusia di atas 60 tahun secara konsekutif. Derajat delirium diukur dengan Memorial Delirium Assesment Scale (MDAS) dan Charlson’s-Age Comorbidity Index (CACI). Pasien tersebut diikuti secara berkala kemudian ditentukan luaran yang buruk yaitu kematian saat dirawat. Hubungan antara derajat keparahan delirium dengan luaran klinis dievaluasi menggunakan uji Pearson. Hasil dikatakan bermakna apabila nilai p<0.05 pada SPSS versi 21 untuk Windows.Hasil: Prevalensi delirium di RSUP Sanglah yakni delirium ringan (48,4%), delirium sedang (28,1%), dan delirium berat (23,4%). Terdapat perbedaan bermakna prevalensi derajat delirium berdasarkan umur (p<0,05), namun tidak pada jenis kelamin (p=0,752). Terdapat perbedaan bermakna pada insiden kematian berdasarkan umur (p=0,045) dan derajat delirium (p=0,01). Terdapat korelasi positif sedang antara derajat delirium dengan insiden kematian (p=0,02; r=0,373).Kesimpulan: Terdapat hubungan yang signifikan antara derajat delirium dengan insiden kematian pada pasien geriatri yang dirawat di RSUP Sanglah.